2018
DOI: 10.1155/2018/5320827
|View full text |Cite
|
Sign up to set email alerts
|

Basic Coagulation Parameters among Human Immunodeficiency Virus-Infected Adults in Gondar, Northwest Ethiopia: A Comparative Cross-Sectional Study

Abstract: Objective We aimed at assessing the basic coagulation parameters of HIV-infected adults at the University of Gondar Hospital antiretroviral therapy clinic. Methods A comparative cross-sectional study was conducted from February to May 2017. A total of 300 study participants, consisting of 100 HAART-naïve HIV-infected adults, 100 HIV-infected adults who were taking HAART, and 100 HIV-seronegative apparently healthy adults, were included. Basic coagulation functional assays such as PT, APTT, and INR were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
5
9
0
Order By: Relevance
“…Due to haematological, hemorrhagic, and thrombotic clinical changes caused by HIV infection, coagulation tests such as PT / INR and aPTT are often considered as global hemostatic markers. A reduction in clotting time in these tests has been associated with hypercoagulability.PT, APTT, and INR were significantly higher, whereas platelet count was significantly lower in HIV-infected adults (both who were taking HAART and HAART-naïve) than HIVseronegative adults (P<0.001) [58]. We do not know in the medical literature references about the normal range in the elderly or if the values are different from the general population.The exception is when they have vascular diseases such as hypertension and diabetes, use of heart prostheses, hepato-intestinal diseases.…”
Section: Discussionmentioning
confidence: 73%
“…Due to haematological, hemorrhagic, and thrombotic clinical changes caused by HIV infection, coagulation tests such as PT / INR and aPTT are often considered as global hemostatic markers. A reduction in clotting time in these tests has been associated with hypercoagulability.PT, APTT, and INR were significantly higher, whereas platelet count was significantly lower in HIV-infected adults (both who were taking HAART and HAART-naïve) than HIVseronegative adults (P<0.001) [58]. We do not know in the medical literature references about the normal range in the elderly or if the values are different from the general population.The exception is when they have vascular diseases such as hypertension and diabetes, use of heart prostheses, hepato-intestinal diseases.…”
Section: Discussionmentioning
confidence: 73%
“…A previous study reported that the contact activation coagulation pathway in PLWH was overactive despite cART and immune reconstitution 22 . In contrast, two studies conducted in African settings found prolonged APTT in PLWH compared to uninfected controls 13 , 20 . These findings may be explained by inclusion of PLWH with late stage disease and consumption of coagulation factors due to endothelial dysfunction or impaired liver synthesis in the latter studies 13 , 26 , 27 .…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, two studies conducted in African settings found prolonged APTT in PLWH compared to uninfected controls 13 , 20 . These findings may be explained by inclusion of PLWH with late stage disease and consumption of coagulation factors due to endothelial dysfunction or impaired liver synthesis in the latter studies 13 , 26 , 27 . In studies including both treated PLWH and uninfected controls, findings have been inconsistent with regard to possible associations between HIV and APTT 13 , 20 , 22 .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations